Graphene oxide as a catalyst for the diastereoselective transfer hydrogenation in the synthesis of prostaglandin derivatives. Issue 74 (1st September 2017) - Coman, Simona M.; Podolean, Iunia; Tudorache, Madalina; Cojocaru, Bogdan; Parvulescu, Vasile I.; Puche, Marta; Garcia, Hermenegildo
Abstract : Modification of GO by organic molecules changes its catalytic activity in the hydrogen transfer from i-propanol to enones, affecting the selectivity to allyl alcohol and diastereoselectivity to the resulting stereoisomers. Abstract : Modification of GO by organic molecules changes its catalytic activity in the hydrogen transfer from i-propanol to enones, affecting the selectivity to allyl alcohol and diastereoselectivity to the resulting stereoisomers. It is noteworthy the system does not contain metals and is recyclable.